CAMPUR KODE: BERBAURNYA RAGAM BAHASA DALAM KEUTUHAN KONTEKS DAN MAKNA - Made Suardika Jaya (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2022)
Code mixing is a common thing in various spoken languages. Through this process, speakers can convey an utterance consisting of two or more languages. Code mixing can be caused by several factors, mainly through the social aspect where one interacts with many people with different backgrounds. Code mixing has many benefits, especially it can make speakers understand and choose the right diction related to something, both in the realm of regional languages or foreign languages, which of course must be adapted to the situation and conditions when communication occurs. Keywords: code mixing, spoken language, social interaction, communication